Development and therapeutic potential of 2-aminothiazole derivatives in anticancer drug discovery - Alizadeh, Seyedeh Roya (Med Chem Res, 2021)
Currently, the development of anticancer drug resistance is significantly restricted the clinical efficacy of the most commonly prescribed anticancer drug. Malignant disease is widely prevalent and considered to be the major challenges of this century, which concerns the medical community all over the world. Consequently, investigating small molecule antitumor agents, which could decrease drug resistance and reduce unpleasant side effect is more desirable. 2-aminothiazole scaffold has emerged as a promising scaffold in medicinal chemistry and drug discovery research. This nucleus is a fundamental part of some clinically applied anticancer drugs such as dasatinib and alpelisib. Literature survey documented that different 2-aminothiazole analogs exhibited their potent and selective nanomolar inhibitory activity against a wide range of human cancerous cell lines such as breast, leukemia, lung, colon, CNS, melanoma, ovarian, renal, and prostate. In this paper, we have reviewed the progresses and structural modification of 2-aminothiazole to pursuit potent anticancers and also highlighted in vitro activities and in silico studies. The information will useful for future innovation. [Figure: see text]